From multilevel governance to the «Memorandum». The chronicle of a fully anticipated crisis - Αρανίτου Βάλια; Παπαβλασόπουλος Ευθύμης; Σπουρδαλάκης Μιχάλης (The Greek Review of Social Research, 2011)
The article begins with the hypothesis that the current crisis cannot be unilaterally attributed to the excesses and/or pathogeneses of the «Metapolitefsi» political arrangement. Rather, the crisis is inherent in the logic of the «modernization » and «reforms» programs that had appeared systematically in the mid-1990s and which have been crystallized within the commitments emerging from the «Memorandum of Economic and Financial Policies». Within this framework of analysis, the article outlines the structural and functional transformations that the political system has undergone and re-examines the main «reform» policies. The goal here is to propose a framework of analysis for an understanding and evaluation of the developments that have taken place in the relationships between the state, society and the market over the last twenty years. These developments, it is argued, precluded both the crisis and its management. Within this context, an attempt is made to evaluate the consequences of these transformations for the reproduction of the socio-political system; as well as the challenges to social cohesion and the legitimacy of political power.